Collaborative consumption, social distance and the extended self. Issue 4 (24th March 2020) - Frechette, Michael; Arnold, Mark; Kaikati, Andrew; Singh, Nitish
Abstract : Purpose: This paper aims to look at the exchange context of peer-to-peer (P2P) collaborative consumption (e.g. Uber and Airbnb). Specifically, the paper examines the effect that the sharing of a personal possession, such as a car or apartment, may have on the consumer. Design/methodology/approach: Two studies were conducted via online surveys. The surveys used vignettes that asked participants to imagine service experiences in either a P2P or a business-to-consumer (B2C) context. The participants then answered questions, including their perceptions of social closeness to the service provider, as well as willingness to pay (Study 1) and expectations of satisfaction (Study 2). The analysis used bootstrapping regression models to examine the relationships. Findings: In both studies, the participants in the P2P conditions reported significantly greater perceived social closeness to the service provider than did those in the B2C condition. The P2P condition also resulted in significant indirect effects (i.e. mediated by social closeness) on willingness to pay (Study 1) and expectations of satisfaction (Study 2). Originality/value: This paper extends the work on social distance to show that the effects are activated by the P2P exchange context. Also demonstrated here is that social closeness acts as an important mediator in the P2P context, affecting outcomes in the consumption and pre-consumption stages. Finally, construal level effects are extended to show that trend interpretation can be influenced by social distance.